Coping da enfermagem diante da morte e morrer de pacientes em cuidados paliativos na Unidade de Terapia Intensiva - Martins, Dayane Franco (2024)
This study focused on the coping strategies used by nursing staff when facing the process of death in Adult Intensive Care Units (ICUs). The topic is situated within the field of Health Psychology as part of the broader study of hospital care. The study's general objective was to understand the coping strategies employed by nurses in the ICU. Specifically, it aimed to: (a) Identify the coping strategies that nurses develop when dealing with the death of patients in Adult ICUs; (b) Describe the feelings and well-being of nurses in the face of death in the Adult ICU; and (c) Determine if and how the conception of death has changed in the context of palliative care experiences in the ICU. A mixed-methods, quali-quantitative, descriptive, and observational design was used. The research involved five intensive care nurses; the instruments included semi-structured interviews and the Coping with Death Scale and the Modes of Coping Scale (EMEP). The results from the Coping with Death Scale showed a slight variation, with means indicating a greater focus on patient death (Factor 1: M=55.8) compared to their own death (Factor 2: M=54). On the EMEP scale, the highest means were in Spiritual (M=76.6) and Social (M=73.6), suggesting that nurses seek coping strategies in these areas. In the discussion, it was observed that despite the emotional challenges, nurses found satisfaction in supporting patients and their families, learning to humanize care and partially cope with their emotional suffering. They faced feelings such as sadness, anguish, and guilt, revealing a fear of showing weakness. The study highlighted the difficulty nurses have in managing their emotions and the emotional connection that arises when caring for critically ill and palliative care patients. This emotional burden, particularly when dealing with death, can affect them in the long term, influencing how they handle challenging end-of-life situations. Nurses expressed a range of feelings, including relief, due to the suffering they witnessed, finding strength in viewing death as the end of the patient's suffering and, consequently, their own. This allowed them to experience grief not as a problem but as a resolution. The interviews did not clearly indicate whether their responses to death were influenced by their professional identity as leaders, which might compel them to display self-confidence, or if they simply found it difficult to know how to act in the face of grief. However, the fear of showing weakness was evident in their perceptions. In conclusion, it is crucial to create spaces for dialogue about death in the workplace, providing tools to manage emotions and reactions in this context.